The Case Study of Two Girls with Gender Dysphoria. Issue 1 (31st December 2023) - Beatrice, James
ABSTRACT: This paper presents the psychoanalysis of two girls, aged five and 11, both self-described as boys. The first case depicts the incoherence and discontinuity of a core sense of being female with depersonalization, identity confusion, and self-sacrifice. The second case describes gender role identification conflicts. Both children presented as males to protect a disavowed female self. However, their etiology was distinctly different. Gender dysphoria proved to be highly complex. Reliance on the developmental lines of self and gender informed clinical interventions. Merger and twinship transferences were essential for establishing a stable personal identity for these children.